Profil Adiksi Media Sosial pada Siswa dan Implikasinya bagi Bimbingan dan Konseling - Pramudya, Mochamad Ikhsan; Istiadah, Feida Noorlaila; Sulistiana, Dewang (Universitas Negeri Gorontalo, 2025)
This research was conducted to describe the profile of social media addiction in class X students at SMAN 10 Tasikmalaya. The research method used is a descriptive method with a quantitative approach, using the entire student population of 442 students as the research sample. The research results show that the majority of students spend a lot of time on social media platforms and ignore daily activities. The most dominant aspect of social media addiction is tolerance, followed by returning to old habits (relapse) and withdrawal symptoms. Social media addiction can have a negative impact on students' mental health and productivity. There is a significant difference in the level of social media addiction between male and female students. Therefore, there is a need for guidance and counseling services using Classical Guidance techniques to reduce the level of addiction in students. In addition, it is important to provide education and support to students and involve families and schools in addressing the problem of social media addiction.